The Identification of a Planar Magnetic Structure within the ICME Shock Sheath and Its influence on Galactic Cosmic-Ray Flux - Shaikh, Zubair I.; Raghav, Anil N.; Vichare, Geeta; Bhaskar, Ankush; Mishra, Wageesh (My University, 2018)
A Forbush decrease is a sudden decrease in cosmic-ray intensity caused by transient interplanetary disturbances. The substructure of an interplanetary counterpart of a coronal mass ejection (ICME) such as a shock sheath and/or a magnetic cloud independently contributes to cosmic-ray decrease, which is evident as a two-step decrease. Our earlier work has shown multistep decrease and recovery within the ICME-driven shock-sheath region. Further, we have suggested that the presence of a small-scale flux rope within the shock-sheath region causes a steady/gradual recovery in cosmic-ray intensity. Here, we demonstrate the presence of a planar magnetic structure (PMS) and small-scale flux rope within a single shock sheath of an ICME. The plot of the elevation (θ) versus azimuthal (phgr) angle of the interplanetary magnetic field (IMF) is used for the identification of the PMS. The planarity, efficiency, and a plane-normal vector are estimated by employing a minimum variance analysis (MVA) technique, which confirmed the presence of the PMS. In addition, a 2D-hodogram method in conjunction with the MVA technique is utilized to identify the flux-rope structure and turbulent conditions in the corresponding ICME region. The observation in the visible suggests that the PMS region within the ICME shock sheath caused the decrease in the cosmic-ray flux observed at Earth. It has also been observed that the sharp variations in the IMF (i.e., turbulence) cause a decrease, whereas the flux-rope structure is responsible for the recovery of the CR flux. Further studies are needed to investigate their origins and to confirm their effects on space weather.
Keywords: Coronal mass ejection; Cosmic rays; Magnetic fields; Solar wind; Sun; Turbulence; CMEs